Illegal traficking of waste electrical and electronic equipment - Pisarić Milana (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2014)
Over the past decade, the problem of used and discarded electrical and electronic devices is increasingly in the focus of governments', NGOs' and the media's attention. In addition to concerns about the volume of waste and the potential risks to human health and the environment from improper management, a topic that has caused the most concern is the cross-border movement of discarded electrical and electronic equipment and their placement in underdeveloped countries and developing countries. This attention has resulted in regulations at the local, national, regional and international levels, including provisions relating to the collection, treatment and export of electronic products. Illegal trade and disposal is particularly dangerous if it is taken into account that these illegal activites are often linked to organized crime in connection with other serious crimes against health, environment and economy.